Practical requirements for the successful implementation and subsequent dissemination of the redefined kilogram. (October 2015) - Davidson, Stuart; Berry, James; Marti, Kilian
Abstract: The kilogram is the last of the seven base units of the SI to be defined in terms of a material artefact rather than by relation to an invariant of nature. Progress is being made towards a redefinition in terms of the Planck constant realised via the watt balance and Avogadro experiments. The accuracy of these experiments is now at the level required by the mass community (2 parts in 10 8 ) and it is likely that the redefinition will be ratified in late 2018. The change to the definition of the kilogram presents issues which need to be addressed in order to effectively implement the redefinition, to ensure continuity of the mass scale and to efficiently disseminate the new definition to the user community. After redefinition the realisation of the SI unit of mass will be possible via either the Avogadro or watt balance approaches. The two experiments work in a vacuum and so a link between mass standards in air (such as the International Prototype Kilogram used to realise the current mass unit) and standards realised in vacuum will need to be established for initially fixing the Planck constant and subsequently for dissemination of the unit of mass. This paper describes research undertaken to prepare for the redefinition. Next generation mass standards, compatible with use in vacuum, have been developed to improve mass stability while optimising vacuum/air transfer characteristics. Methods for the transfer between and storage in vacuum, inert gas and air have been investigated both gravimetrically and using surface analysis techniques such as X-ray photoelectron spectroscopy (XPS) to characterise surface sorption effects. Additionally new cleaning techniques for primary mass standards using UV activated ozone and low pressure plasma have been developed to replace current manual cleaning methods. The implementation of this research will ensure the maximum benefit is realised from the redefinition of the kilogram in terms of a fundamental constant. Highlights: An examination of potential materials for next-generation mass standards. Determines the effect of transfer between air and vacuum on primary mass standards. Outlines new techniques for the repeatable cleaning of masses. Investigates storage methods to improve the long term stability of masses.